2021
DOI: 10.1055/s-0040-1721461
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Success of Metal Endobronchial Stents in Lung Transplant Recipients

Abstract: Background Bronchial stenosis is a common complication following lung transplantation. We evaluated long-term associations of the use of self-expandable metal stents (SEMSs) with lung function tests, patient safety, and survival. Methods A retrospective chart review of 582 lung transplantations performed at our institution between January 2002 and January 2018. Fifty-four patients with SEMSs (intervention group) were matched one-to-one to patients without SEMSs (control group) using propensity score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Almost all studies indicated that stent insertion could immediately palliate stenosis symptoms such as dyspnoea, improve lung function ( 11 , 13 16 , 19 21 , 23 26 ), decrease the degree of stenosis ( 23 ) and successfully re-open the airways ( 16 ). Regarding long-term efficacy, most studies indicated that the survival time of post-stent patients was similar to that of patients without stents ( 3 , 11 , 20 , 24 , 25 ). However, Gottlieb et al ( 16 ) reported significantly lower survival rate in LTx recipients with stents than in the total LTx cohort.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Almost all studies indicated that stent insertion could immediately palliate stenosis symptoms such as dyspnoea, improve lung function ( 11 , 13 16 , 19 21 , 23 26 ), decrease the degree of stenosis ( 23 ) and successfully re-open the airways ( 16 ). Regarding long-term efficacy, most studies indicated that the survival time of post-stent patients was similar to that of patients without stents ( 3 , 11 , 20 , 24 , 25 ). However, Gottlieb et al ( 16 ) reported significantly lower survival rate in LTx recipients with stents than in the total LTx cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Ma et al ( 21 ) found a statistically significant reduction in the number of bronchoscopies per month after stent removal compared to pre-stent placement for patients who ultimately could undergo stent removal. Regarding long-term lung function improvement for more than 3 months, some studies demonstrated that FEV 1 improved significantly after stent implantation ( 11 , 14 , 19 , 21 , 24 , 26 ). However, Izhakian et al ( 24 ) suggested that FEV 1 values were significantly lower in patients with stents than those without stents at 2.5 years post-transplantation but did not differ significantly between the two groups at 5, 7.5, and 10 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This technique is based on previous works which have demonstrated since 1997 in animals and then in humans the interest of using stented aortic matrices for airway replacement (21,22). Izhakian et al demonstrated that SEMS insertion was associated with a positive sustained effect on lung function without increasing long-term mortality (23). In addition, they established that bronchial stents were more likely to be colonized with pathologic bacteria and having pneumonia (24).…”
mentioning
confidence: 99%